PENGEMBANGAN VIDEO EDUKASI ANTISIPASI GEMPA BUMI MENGGUNAKAN METODE MOTION GRAPHIC - Ghita Octarisa Angelia (Hemispheres Press, 2023)
Earthquakes are natural phenomena that frequently occur in various parts of the world. To enhance public awareness about the importance of understanding and preparing for earthquakes, the use of educational videos has become a popular approach. In this study, we propose the development of an educational video using the motion graphic technique to improve the effectiveness of the messages conveyed to the audience. This research focuses on the development of an educational video that visually explains the steps for earthquake preparedness using captivating motion graphic techniques. The motion graphic method utilizes animations, moving graphics, and other visual effects to simplify and present complex concepts and information in an engaging manner. The aim is to enable the audience, particularly children and teenagers, to easily comprehend the information and necessary actions during an earthquake. Keywords : Earthquakes, Motion graphic, Education